SAT0479 IMPACT OF TRABECULAR BONE SCORE ON INTERVENTION THRESHOLD FOR BONE SPARING THERAPY IN PATIENTS REFERRED FOR BONE MINERAL DENSITY. (2nd June 2020) - Rakieh, C.; Ho, S.; Butler, R.
Abstract : Background: Trabecular bone score (TBS) is an index of skeletal quality that has been validated as an independent risk factor for fracture and incorporated into fracture risk assessment (FRAX). TBS provides information on bone microarchitecture not captured from standard bone mineral density (BMD) measured by dual energy X-ray absorptiometry (DXA). Nonetheless, the clinical implications of using TBS in routine practice are not yet fully understood and warrant further evaluation. Objectives: To determine whether lumbar TBS can have an impact on clinician's treatment threshold derived from DXA and clinical risk factors: does the addition of TBS to DXA measurements make the clinician more or less likely to recommend bone sparing therapy? Methods: A cross-sectional study at a tertiary metabolic bone centre in the West Midlands region of England. Three expert metabolic bone physicians, two rheumatologists and one elderly care, assessed consecutive patients referred for a DXA scan ± clinic review and provided treatment recommendations with and without TBS. Patients ≥ 18 years old with BMI of 15-37 who were not on bone sparing therapy were considered eligible. TBS was defined according to T-score as normal (T-score ≥ -1), moderate (-1 > T-score ≥ -2.5) or degraded (T-score ≤ -2.5). TBS groups were stratified by BMD T-scores (normal, osteopenia, or osteoporosis) using minimum T-score of total hip, femoral neck, and spine to identify categories in which TBS may be of more clinical use. The main outcome measure was the proportion of change in clinician's treatment threshold between BMD alone and BMD plus TBS. The difference was assessed for significance using Chi-square test. Additionally, the change in UK National Osteoporosis Guideline Group (NOGG) threshold was also assessed using TBS-adjusted FRAX scores. Correlations between BMD-TBS strata and the change in intervention threshold (yes/no) were carried out using Spearman test. Results: 540 patients were analysed. The inclusion of TBS resulted in 8.2% change in clinician's treatment threshold (p <0.001) shifting the outcome 6.5 % for and 1.7 % against treatment. More than half of the cases in which the clinical decision was changed were for patients with osteopenia and degraded TBS (significant correlation; P <0.001). NOGG intervention threshold was changed in 7.4% of the cases (P<0.001); 6.1% for and 1.3% against treatment. 37.5% of NOGG changed outcome was related to osteopenia with degraded TBS (p<0.001). Kappa agreement between the clinician and NOGG was fair at 0.42 (p<0.001). Conclusion: These results demonstrate that using TBS in routine clinical practice is most likely to impact treatment decision in patients with osteopenia who have compromised bone microarchitecture. Incorporating TBS in routine DXA scans may lead to a net increase in bone protective therapy of approximately 5%. It is unknown whether adopting such an approach universally can reduce future fracture risk, and prospective studies are needed to address this question. References: [1]Hans D et al. J Bone Miner Res. 2011;26(11):2762-9. [2]McCloskey EV et al. Calcif Tissue Int. 2015;96(6):500-9. Acknowledgments: Bone density unit &Rheumatology team, Robert Jones and Agnes Hunt Orthopaedic Hospital Disclosure of Interests: None declared